Intensidad de luz solar en el rendimiento de Lactuca sativa L. en un sistema hidropónico. Loreto. 2021 - Angeles Navarro, William Enrique (2022)
Lettuce is one of the olive species that is most cultivated in the Amazon of all the vegetables and the majority in traditional systems; the hydroponic technique can improve its vegetative adaptation in the Loreto region, the main objective was to determine the effect of sunlight intensity on the yield of Lactuca sativa L. in a hydroponic system. The aim is to improve the genetic potential when cultivating in systems of laminar flow of nutrients under climatic conditions in the tropics. The completely randomized design was used with the treatments: Without shade and with 35% shade. The transplant of seedlings grown in a hydroponic box was carried out at the age of 15 days with an average height of 8 cm, the definitive management was in 3” diameter PVC tubes at a distance between plants of 0.20 m and between tubes of 0.20 m. The shaded crop showed statistical significance for plant height and width with means of 24.30, 17.43 cm and 25.30, 19.72 cm. The crop without shading also showed statistical significance for stem diameter and root length with means of 10.20, 9.07 and 7.63 cm. 2.5" There is no evidence of light intensity effect for number of leaves, weight of roots and weight of plant, being numerically higher without shading for number of leaves and weight of roots with means of 10.90, 10.07 g and 8.60, 8.27 g; while the weight of the plant occupies the first place with shading with an average of 51.93 and 50.13 g.